2023
DOI: 10.1139/cjss-2022-0094
|View full text |Cite
|
Sign up to set email alerts
|

Short-term response of soil aggregate stability and labile carbon to contour tillage, diversion terrace, grassed waterway, and tile drainage implementation

Abstract: Soil degradation has been of great concern for New Brunswick’s potato farmers, especially on sloped land and shallow soils. In this study we evaluated the initial response of labile soil carbon (C) fractions (permanganate oxidizable C – POXC; and particulate organic C – POC) and aggregate stability to two integrated best management practices (BMPIs) comprised of the following individual practices: diversion terraces (DT), grassed waterways (GW), and contour tillage (CT) [i.e., DTGW] and DT, GW, CT, and tile dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 43 publications
0
0
1
Order By: Relevance
“…In contrast, the cumulative effects of water flow and retention manifest themselves at the DTW > 0.25 ha and log 10 (DTW > 0.25 ha) scales, with the former and latter pertaining to soil moisture content and Mehlich-3 element concentrations, respectively. In contrast, TOC % was not related to DTW in this study, but the reported uphill-to-downhill TOC % variations [30] [32] [33] likely vary at the DTW > 4 ha scale as well.…”
Section: Discussioncontrasting
confidence: 60%
“…In contrast, the cumulative effects of water flow and retention manifest themselves at the DTW > 0.25 ha and log 10 (DTW > 0.25 ha) scales, with the former and latter pertaining to soil moisture content and Mehlich-3 element concentrations, respectively. In contrast, TOC % was not related to DTW in this study, but the reported uphill-to-downhill TOC % variations [30] [32] [33] likely vary at the DTW > 4 ha scale as well.…”
Section: Discussioncontrasting
confidence: 60%